RETRACTED: Green finance strategies for mitigating GHG emissions in China: Public spending as a new determinant of green economic development - Xia, Lianfeng; Liu, Yujia; Tian, Yunqing (Frontiers in Environmental Science, 2022)
In order to lessen China’s carbon footprint, the government has turned to environmentally friendly financing. A reduction in CO2 has been reported in some Chinese provinces where green finance has been developed. Numerous regions in China from 2010 to 2020 are selected for this study. Based on a Dynamic Seemingly Uncorrelated, fully modified ordinary least squares and dynamic ordinary least squares regressions model, empirical research is performed with per capita growth in the economy, public spending, and the relationship between economic growth, human resources, and industrial arrangement as core variables to test the influence of green financing on CO2 emission in Chinese provinces. According to the findings, green financing speeds up the reduction of carbon emissions. Moreover, the outcomes present that industrial structure, economic growth per capita, and trade openness increase carbon emissions. Likewise, public expenditures and human capital are significantly contributing to emissions reduction. The findings show that sustainable green environment can only be achieved by boosting the performance of green finance and increasing the level of green finance supported by the Chinese economy. Last but not least, policymakers should promote public health and education spending to fully engage in the protection of the environmental efforts to encourage green consumption while minimizing the structural problems resulting from economic activity.